Conselho de classe e série como espaço de formação: um estudo na perspectiva sócio-histórica - Oliveira, Maria Magda Vaz de (2022)
This research was drawn by the necessity to understand the movement of determinations that led education to promote practices that are distant from Theory and to have turned learning instruments, such as Collective Pedagogical Work Classes(ATPC) and Class Councils (CCS), into bureaucratic instances which do not fulfill their objective to provide reflection and collective construction learning moments, so important when it comes to the use of public resources. The main objective of this research was to get to know which processes were necessary to constitute the CCS, within the Public Educational System of the State of São Paulo, to evaluate conditionsand possibilities to transform it in a teacher training space. Specific objectives are to know how the CCS activities are historically characterized, to recognize its actors andthe role they play, and to identify how related legislation is applied to it. This study wasbased on Socio-historical psychology, notably on the production of Vygotsky about learning and educational processes, especially on the Zone of Proximal Development(ZDI). Theoretical material was based on specific references aimed at knowing whichsocial contexts allowed the implementation of the CCS in Brazil in the end of 1980’s, then becoming important part of the process of implementation of Democratic Management at schools. Information was produced with a semi-structured online interview with one teacher. This teacher, subject of this research, was working both atthe Public Educational System of the State and the City of São Paulo. Results showedthe historically reduced presence of CCS in Brazilian education, its distortions as a democratic mechanism of teacher and community training; on the other hand, CCS potentialities to build practical agenda for qualitative change for students, teachers, and community were revealed. We also noticed how wide such changes can be to promote greater commitment, in order to contribute with schools’ teaching and learningprocesses. This way, we understood the role of CCS for building proficient and profound relationships between students and teachers, creating a solid base for developing democratic principles and practices, enhancing the capacity of school as alearning organization